The Effects of Resistance and Endurance Training on the Liver Tissue FNDC5 mRNA Gene Expression in Male Rats - Amir Rashidlamir; Mohammad Hoseinzadeh; Leili Zeiaddini Dashtkhaki (The Society of Aging and Physical Activity (SAPA), 2017)
Background. The accumulation of excess triglyceride in the liver and a decrease in brown adipose tissue is related to the fatty liver disease. Regular physical activity can take part in regulating fat oxidation and inhibiting fat accumulation by creating and releasing some myokines. Nevertheless, the effectiveness of each training method in this regard is still not certain. Objective(s). This study aims at comparing the effects of resistance and endurance training on FNDC5 (the precursor of irisin myokine) gene expression in male rat liver tissues.. Methods. Fifteen Wistar male rats (aged 10-12 weeks with an average weight of 331.8 ±63.09 gr) were used. After being taken to the animals' laboratory, the subjects were randomly assigned to three equal groups viz: control (N=5), endurance (N=5) and resistance (N=5). For the purpose of tissue sampling, all these subjects were anesthetized 72 hours after the experiment had been completed. The liver tissue was immediately removed and then quickly frozen in liquid nitrogen and kept at a temperature of -80o C until RNA extraction. FNDC5 relative gene expression was identified by Real-time PCR method. Results. Data analysis revealed a significant difference in FNDC5 gene expression among the groups (P=0.008, Chi Square=31.791). No significant difference was observed between the resistance training and endurance training groups in FNDC5 gene expression, though (P=0.959). Conclusion. It can be established that both resistance and endurance training can similarly affect the production and secretion of exercise-induced myokines, including FNDC5 irisin, which can in turn protect against obesity and its impacts on the liver tissue by stimulating the process of browning of white fat.